2022
DOI: 10.12998/wjcc.v10.i4.1242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical performance of i-gel and Ambu laryngeal masks in anaesthetised paediatric patients: A meta-analysis

Abstract: BACKGROUND Paediatric supraglottic airway devices (SGAs) are widely used in routine anaesthesia and serve as primary or back-up devices for difficult airway management. The inflatable Ambu laryngeal masks and non-inflatable i-gel are two improvements of SGAs based on classic laryngeal masks. The clinical performance and safety of these two devices in paediatric patients are still unclear and warrant further investigation. AIM To perform a systematic review and meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Because of the less stimulation of the laryngeal mask which allowed reduction of anesthetics and free of muscle relaxant, and advantages for difficult airway management compared to endotracheal tube, we took it as the first choice for airway management. Previous studies had shown that inflatable and non-inflatable laryngeal masks could provide equal ventilation quality, and the i-gel presented a better sealing effect [4,5]. Meanwhile, the gellaryngeal mask is the most commonly used LMA in our center which usually provides very high seal pressure as good as inflatable LMAs.…”
Section: Discussionmentioning
confidence: 90%
“…Because of the less stimulation of the laryngeal mask which allowed reduction of anesthetics and free of muscle relaxant, and advantages for difficult airway management compared to endotracheal tube, we took it as the first choice for airway management. Previous studies had shown that inflatable and non-inflatable laryngeal masks could provide equal ventilation quality, and the i-gel presented a better sealing effect [4,5]. Meanwhile, the gellaryngeal mask is the most commonly used LMA in our center which usually provides very high seal pressure as good as inflatable LMAs.…”
Section: Discussionmentioning
confidence: 90%
“…The OLP is an important index for evaluating the effectiveness and safety of laryngeal mask ventilation and is of great significance in maintaining airway tightness, ensuring ventilation, and reducing the entry of oropharyngeal and gastric contents into the respiratory tract. [10][11][12][13] OLP results from a tight surface-to-surface fit between the laryngeal mask and soft tissue surrounding the glottis. The study of Ambu AuraFlex laryngeal mask by Liu et al [2] showed that when the intracapsular pressure reached 30 cm H 2 O, the OLP could reach 19 to 20 cm H 2 O, which could meet the ventilation needs of pediatric ophthalmic surgery anesthesia.…”
Section: Discussionmentioning
confidence: 99%